Microneedle Array Patch Made of Kangfuxin/Chitosan/Fucoidan Complex Enables Full-Thickness Wound Healing - Yu, Xixi; Wang, Caixia; Wang, Yuanfei; Li, Longhao; Gao, Xiang; Zhu, Tingting; An, Pugen; Meng, Zhaojian; Wang, Wanchun; Wu, Tong; Hao, Yuanping (Frontiers in Chemistry, 2022)
Skin wound caused by external injury is usually difficult to be cured by conventional topical administration because of its poor drug diffusion across the stratum corneum. It has been recognized that stratum corneum is the major obstacle for transdermal drug delivery. To address this issue, microneedles (MNs) have been developed to penetrate the stratum corneum of the skin and then form micron-sized pores between the epidermis and the dermis layers. As such, biomacromolecule drugs and/or insoluble drug molecules can be allowed for effective transdermal penetration. A multifunctional microneedle array patch that can avoid wound infection and promote tissue remolding has important value for wound healing. Among others, marine polysaccharides have attracted much attention in multifarious biomedical applications due to their excellent (bio)physical and chemical properties. Herein, we developed a microneedle array patch using a blend of kangfuxin (KFX), chitosan (CS), and fucoidan (FD), named KCFMN, for accelerating full-thickness wound healing. The traditional Chinese medicine KFX extracted from Periplaneta americana (PA) has effective bio-functions in promoting wound healing. The macro-/micro-morphology and (bio)physicochemical properties of such composite microneedles were also studied. We showed that the KCFMN patch displayed noticeable antibacterial properties and good cytocompatibility. In particular, the KCFMN patch significantly accelerated the wound healing development in a full-thickness wound in rats by improving the epithelial thickness and collagen deposition. Thus, this versatile KCFMN patch has great prospects as a dressing for full-thickness wound healing.